Aspects of Biological Age Assessment and Its Significance in Ophthalmology - Yu. N. Yusef; Yu. A. Guseynov; M. H. Durzhinskaya (Oftalʹmologiâ, 2024)
This article explores the key aspects of biological age assessment and the potential of studying this parameter in ophthalmology. Biological age, as an indicator of the state of the organism, differs from chronological age and allows for a more accurate evaluation of the functional capabilities of organs and systems. In the context of ophthalmology, this parameter is particularly relevant, as eye health and visual function can vary significantly based on individual patient characteristics, including genetic factors, lifestyle choices, and the presence of comorbid conditions. The article analyzes contemporary methods for assessing biological age, including laboratory and instrumental approaches. It presents data on the impact of biological age on the development of various ophthalmological diseases. The importance of a personalized approach to diagnosis and therapy in ophthalmology is emphasized, taking into account the biological age of the patient. The authors propose the implementation of biological age assessment methods in clinical practice to improve treatment outcome predictions and enhance patients’ quality of life. Further research in this area is necessary to develop new strategies for the prevention and treatment of ophthalmopathologies that consider the parameter of biological age.